INNOVATIVE HUMAN RESOURCE MANAGEMENT (ResearchJet Journal of Analysis and Inventions, 2021)
The function of human resource management in an innovative organization turns into an instrument of a long-term strategy aimed at removing barriers to innovation. The practice of human resource management becomes the link between learning, innovation and creativity. This, of course, requires a fundamentally different approach to the organization of human resource management in an innovative organization. In essence, we are talking about the formation of innovative human resource management (IHRM), which is a border area between two areas of management science and practice: innovative management and human resource management.